Dual functions of imidazole-based polymeric ionic liquid (PIL) on the anticorrosive performance of graphene-based waterborne epoxy coatings. (25th April 2018) - Liu, Chengbao; Du, Peng; Nan, Feng; Zhao, Haichao; Wang, Liping
Abstract: Dispersion of graphene nanosheets in a water and polymer matrix has been rarely achieved due to graphene's hydrophobicity, which thus impedes its potential anticorrosive application. In this study, stable graphene aqueous dispersion was obtained by using imidazole-based polymeric ionic liquid (PIL) as the dispersant with ultrasonic vibration. Stacked graphene sheets were exfoliated to a few layers via cation- π interaction between PIL and graphene nanosheets. Electrochemical impedance measurements were taken to investigate the anticorrosion performance of epoxy coatings with or without polymeric ionic liquid–graphene (PIL–G) hybrids. Results indicated that the PIL–G hybrid significantly enhanced the long-term protective performance of epoxy coatings, which was attributed to the synergistic effects of the corrosion-inhibitive PIL and impermeable graphene nanosheets.